2019
DOI: 10.1101/gad.330134.119
|View full text |Cite
|
Sign up to set email alerts
|

Context-specific regulation of cell survival by a miRNA-controlled BIM rheostat

Abstract: Knockout of the ubiquitously expressed miRNA-17∼92 cluster in mice produces a lethal developmental lung defect, skeletal abnormalities, and blocked B lymphopoiesis. A shared target of miR-17∼92 miRNAs is the pro-apoptotic protein BIM, central to life-death decisions in mammalian cells. To clarify the contribution of miR-17∼92:Bim interactions to the complex miR-17∼92 knockout phenotype, we used a system of conditional mutagenesis of the nine Bim 3 ′ UTR miR-17∼92 seed matches. Blocking miR-17∼92:Bim interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Bim is closely associated with the development and treatment of autoimmune diseases, degenerative diseases and tumors. Previous studies have demonstrated that Bim is a target gene for multiple mirnas (41,42). Previous studies have shown that Bim is a putative mir-24 target (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Bim is closely associated with the development and treatment of autoimmune diseases, degenerative diseases and tumors. Previous studies have demonstrated that Bim is a target gene for multiple mirnas (41,42). Previous studies have shown that Bim is a putative mir-24 target (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, lung development was exclusively dependent on the miR-17∼92/Bim axis (58). These experiments highlight the likely sparseness of "master targets, " although their existence might be partially obscured by the time consuming and almost exceedingly vast experimental effort, given that each miRNA has hundreds of theoretically predicted targets.…”
Section: "Master Targets" Vs Coordinated Mrna Targeting Vs Indirectmentioning
confidence: 91%
“…Notably, neither heterozygous nor homozygous loss of Pten rescued the effects of miR-17∼92-deficiency in Treg cells (51). Furthermore, disruption of miR-17∼92 MREs in Bim had almost no effect on B-cell development, despite a prominent role of Bim in apoptosis of B-lineage cells (57)(58)(59).…”
Section: "Master Targets" Vs Coordinated Mrna Targeting Vs Indirectmentioning
confidence: 98%
See 1 more Smart Citation
“…These use integration of reporters 13,14 or injection of RNA libraries 15,16 and therefore do not evaluate endogenous phenotypes, or are restricted to one stage of the animal life cycle. Classical genome editing by injection, now widely accessible due to CRISPR-Cas 17,18 , has enabled endogenous functional tests, but is still work-intensive and limited in scalability 19,20 .…”
Section: Introductionmentioning
confidence: 99%